Relation between 1,500-m running performance and running economy during high-intensity running in well-trained distance runners - Tanji, F.; Shirai, Y.; Tsuji, T.; Shimazu, W.; Nabekura, Y. (The Journal of Physical Fitness and Sports Medicine, 2017)
Running economy (RE), which is evaluated at an exercise intensity below the lactate threshold (LT), is recognized as the most important physiological variable for estimating running performance. However, middle- and long-distance athletes run above LT intensity during their competitive events. This study elucidates the relation between 1,500-m running performance and physiological variables, including RE measured at intensities below and above the LT. The study included 34 male distance runners (1,500-m velocity: 22.2 ± 0.8 km·h-1, equivalent to race times of 4'03?2 ± 8?5). RE was calculated at four running velocities selected to provide intensities of 90%LT and 95%LT below LT (REbLT) and 105%LT and 110%LT above LT (REaLT). RE was determined from aerobic energy metabolism, calculated from oxygen uptake and the respiratory exchange ratio, combined with anaerobic energy metabolism, calculated from the change in blood lactate concentration. Results show that the 1,500-m velocity was not related to maximal oxygen uptake (VO2max) or LT intensity (r = 0.19 and 0.10, respectively). This velocity correlated with both REaLT and REbLT, with the correlation coefficient being higher for REaLT (r = -0.65 and -0.71 vs -0.56 and -0.58). Furthermore, the coefficient of determination for 1,500-m velocity determined from VO2max, LT intensity and REaLT was higher than that determined from VO2max, LT intensity and REbLT (R2 = 0.603 and 0.640 vs 0.415 and 0.543). These results suggest that RE measured at an intensity above LT intensity may be better than other physiological variables for estimating 1,500-m running performance.